Demonstrating results : using outcome measurement in your library - Rubin, Rhea Joyce (PLA results series., 2006)
Library services and programs that not only meet goals but can also demonstrate these results are more likely to secure repeat funding. By evaluating and presenting outcomes, libraries can document the positive work they do in a concrete way and gain financial support. According to Planning for Results expert Rubin, outcome measurement lets libraries evaluate how they affect their users' quality of life. This latest addition to the PLA-sponsored Results Series uses familiar task breakdowns along with key terms in a step-by-step, service-oriented format so that readers can master the outcome me.